29 Demonstrating the Effects of Deworming and Implanting Weaned Calves for Retained Ownership on Pasture in Eastern Oklahoma. (28th November 2020) - Beck, Paul A; Ward, Earl; Clawson, Scott; Pugh, Brian; Farris, Rodney
Abstract: The majority of cow-calf producers in Oklahoma sell their calves at weaning. Preconditioning and retained ownership through the stocker phase provides economic benefits to these operations. The objectives of this demonstration were to illustrate the benefits of growth promoting technologies for calves post-weaning. Calves (n = 39 heifers and 24 steers; BW = 229 ± 23.9 kg) from the OSU Eastern Research Station cowherd were weaned on day – 20 (April 15) and preconditioned. On day 0 (May 6), calves (n = 20 heifers and 12 steers) were treated for internal parasites (Dectomax, Zoetis Animal Health) and evenly allocated to 2 Bermudagrass/tall fescue pastures (9.5 ± 1.42 ha) for 143 days. The remaining calves (n = 19 heifers and 12 steers) were not treated for parasites and allocated to 2 pastures (9.1 ± 1.42 ha). In each pasture, ½ of the calves of each sex were implanted (Synovex-S or Synovex-H, Zoetis). Calves dewormed on day 0 and were dewormed again on day 70 (July 16). Data were analyzed as a split plot experimental design with dewormer treatment as the main plot and calf sex and implant treatment were the split plots. There were no interactions among calf sex, deworming, and implants (P ≥ 0.42). Steers were heavier (P < 0.01) than heifers throughout the summer, but did not have an advantage in gain performance (P ≥ 0.22). Deworming did not impact (P = 0.44) overall growth performance of calves, but did numerically (P = 0.18) increase ADG from day 71 to 143 by 0.15 kg/d. Growth promoting implants increased (P = 0.03) daily gains by 0.09 kg/day in the early summer and over the entire summer by 0.07 kg/day (P < 0.01). The combination of deworming and implants increased (P = 0.01) season long ADG by 0.11 kg/day over unimplanted controls. This demonstration was used to illustrate the potential that growth promoting implants and deworming provides for economically beneficial performance enhancement for retained stocker calves on mixed grass pasture.